Recitation of quran and music to reduce chemotherapy‐induced anxiety among adult patients with cancer: A clinical trial - Al‐Jubouri, Mohammed Baqer Abbas; Isam, Safad Riyadh; Hussein, Shaymaa Mohammed; Machuca‐Contreras, Felipe (Nursing open, 2021)
Aim The aim of this study was to assess the effectiveness of listening to music or Quran in reducing cancer patients’ anxiety before chemotherapy administration. Reducing anxiety in people with cancer, prior to chemotherapy administration, is a crucial goal in nursing care. Design An experimental comparative study was conducted. Methods A simple randomization sampling method was applied. Two hundred thirty‐eight people with cancer who underwent chemotherapy were participated. They are assigned as Quran, music and control groups. Results The overall score of Arabic State Anxiety Inventory in all groups revealed that there was a significant difference between pre‐test and post‐test among participants. Listening to Quran or music reduced the chemotherapy‐induced anxiety. There was no difference between these two ways to reduce anxiety in people with cancer. Listening to Quran or music can be added in nursing care plans prior chemotherapy administrations to reduce cancer patients’ anxiety.